A modified characteristic projection finite element method for the Kelvin-Voigt viscoelastic fluid equations. (1st March 2022) - Si, Zhiyong; Wang, Qing; Wang, Yunxia
Abstract: This paper presents a modified characteristic projection finite element method for the Kelvin-Voigt viscoelastic fluid equations. Then, the unconditional stability and optimal convergence of numerical solutions in L 2 -norms and H 1 -norms were presented. In addition, some numerical results will be given to testify the theoretical analysis. The numerical results show that the convergence orders are optimal, which show the theoretical analysis is right. The numerical results show that our method is robust for different Reynolds numbers. The numerical results imply that the numerical algorithm also converges for different retardation time. It means that our numerical method is robust for different retardation time.